An overview of lane changing model at signalised intersection / Jezan Md Diah, Li Sian Tey and Fathiyah Roslee - Md Diah, Jezan; Li, Sian Tey; Roslee, Fathiyah (UiTM Press, 2016)
In recent years, lane changing has become a crucial issue in traffic engineering and safety aspect due to distribution of vehicles across lanes thus contributing to traffic movements. In order to keep the right route, drivers have to change their lanes. However, lane changing has a high potential of accidents, especially at signalised intersection. This may cause the traffic flow to become heavier and traffic congestion. The aims of this study are to study on lane changing issue at signalised intersection, to determine the factors contributing to lane changing at signalised intersection and to develop a model for improvement of traffic flow in lane changing behaviour at signalised intersection. Lane changing model is important because it will reduce traffic congestion and smoothen the traffic. This study will contribute in studying the changing lane issue at signalised intersection which is to control the flow of traffic in order to ensure the traffic flows smoothly and to reduce traffic congestion especially on the merging issue at signalised intersection.